Puerto Rico-INBRE Metabolomics Research Core - Chorna, Nataliya (J Biomol Tech, 2020)
The PR-INBRE Metabolomics Research Core (MRC) is located at the University of Puerto Rico, Medical Sciences Campus, San Juan, Puerto Rico. The MRC is the only facility of this kind in Puerto Rico available as a shared resource free-of-charge for undergraduate, graduate students, faculty members from INBRE Network universities and beyond who are interested in collaboration with the MRC in the development of new technologies that applied metabolomics approach in Neuroscience, Molecular Medicine, Drug Development, Environmental and Behavioral Sciences. The MRC is also available as a shared resource on a fee-for-service basis for other investigators, industrial laboratories, and clinics. The MRC offers a diverse applications of metabolomics technology for studying and answering biomedical questions related to basic and translational research by offering a scientific seminars and training workshops, support in the developing and optimizing methods for targeted and untargeted detection and quantification of various metabolites ranging from amino acids, organic acids, vitamins, phosphates, sugars, polyamines, alcohols, fatty acids, and sterols using diverse biological matrices including tissues, cells, and biofluids (urine, blood, saliva) via gas chromatography/mass spectrometry. The MRC operates to ensure the best practices and analytical performance of the existed state-of-art instrumentation Shimadzu GC/MS QP2010 and TQ8050 GC/MS/MS. The MRC has established collaborations with other IDeA cores such as the University of Vermont Mass Spectrometry Core and Montana State University Proteomics, Metabolomics and Mass Spectrometry Facility and continue nurturing new and expanding established collaborations with the other investigators and Core facilities. The long-term goal of the MRC is to accelerate the competitiveness of investigators by providing translational research strengths to their discoveries. The MRC is supported by the PR-INBRE (NIGMS P20 GM103475).